2015
DOI: 10.37040/geografie2015120030372
|View full text |Cite
|
Sign up to set email alerts
|

Ukrainian migration in the EU: A comparative analysis of migration and remittance behaviour

Abstract: From the perspective of international migration, Ukraine represents a particularly interesting case because it is a country of emigration, immigration and transit migration; wherefore the movement of people occurs in all directions. Moreover, the country faces serious economic problems that are fuelled by political instability within the country. Nowadays, Ukraine is a country with fifth largest emigration in the world with the largest representation of emigrants in Czechia. This paper examines the remittance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…On the other hand, Ukrainian migration in Europe is quite similar to Mexican migration into the United States (a special case, since migration is getting more diverse including the majority of the country involved in it with multiple U.S. destinations getting more dispersed and targeted by Mexican migrants) (see Kandel, Massey, 2002). One would probably agree that Ukrainian migration in the EU (and in some countries where it is particularly abundant, such as Poland, the Czech Republic, Italy, or Spain) signifies a significant occurrence and special implications for the labour market and national security (see Iglicka, Weinar, 2008;Strielkowski, Weyskrabova, 2014;Ambrosetti et al, 2014;Čajka et al, 2014;Ducháč et al, 2015;Strielkowski et al, 2015;or Van Mol et al, 2018). Moreover, Sanderson et al (2014) focused on the construction sector, because of its significance in the process of new destination creation in the Czech Republic, also found that the Ukrainian migration into the Czech Republic is firmly channelled along occupational lines linking the Ukrainian and Czech construction sectors.…”
Section: Research Objectives and Methodologymentioning
confidence: 99%
“…On the other hand, Ukrainian migration in Europe is quite similar to Mexican migration into the United States (a special case, since migration is getting more diverse including the majority of the country involved in it with multiple U.S. destinations getting more dispersed and targeted by Mexican migrants) (see Kandel, Massey, 2002). One would probably agree that Ukrainian migration in the EU (and in some countries where it is particularly abundant, such as Poland, the Czech Republic, Italy, or Spain) signifies a significant occurrence and special implications for the labour market and national security (see Iglicka, Weinar, 2008;Strielkowski, Weyskrabova, 2014;Ambrosetti et al, 2014;Čajka et al, 2014;Ducháč et al, 2015;Strielkowski et al, 2015;or Van Mol et al, 2018). Moreover, Sanderson et al (2014) focused on the construction sector, because of its significance in the process of new destination creation in the Czech Republic, also found that the Ukrainian migration into the Czech Republic is firmly channelled along occupational lines linking the Ukrainian and Czech construction sectors.…”
Section: Research Objectives and Methodologymentioning
confidence: 99%
“…Glass cliff expression is used analyzing hopeless situations in companies where women leaders manage entities operating in complicated conditions and take C-suite positions in which men leaders have already failed (Glass & Cook, 2016;Ryan et al, 2016). It is more difficult to demonstrate successful leadership in this kind of tough situations also because of double standards applied to women and men leaders (Evans, 2014;Strielkowski et al, 2015;Strielkowski et al, 2016;Strielkowski & Shishkin, 2017;Bordea et al, 2017;Strielkowski & Chigisheva, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%